Aid and the environment in Africa: A synthesis of eight case studies - Edwin Muchapondwa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This study seeks to understand what aid flows have been doing to the environment in eight countries in Eastern, Western and Southern Africa. Total aid to these countries' environmental sectors for the 2000s decade is about US10.17 billion and bilateral aid has been on the rise. There seems to have been a structural change in some countries where donors have been increasing the number of small projects. Aid is perceived to play a significant role in enhancing environmental quality because of constant environmental mainstreaming. Therefore, a general increase in unmarked aid will improve environmental conditions as long as mainstreaming of either biodiversity or climate change or desertification or the environment takes place.
Keywords: F35; O13; Q01; 330; Africa; aid; environment; environmental mainstreaming